Genetic differentiation of common reed (Phragmites australis) populations from selected lakes of Pomerania (NW Poland), revealed by electrophoretically detected peroxidase variability - Krzakowa, Maria; Michalak, Marcin (Biodiversity: Research and Conservation, 2011)
Three populations of common reed (Phragmites australis (Cav) Trin. ex Steud.), growing under differing edaphic conditions in lakes near the town of Koszalin (the Pomerania region in north-western Poland), were studied in respect to frequencies of electrophoretically detected allozymes in two peroxidase loci: a monomeric locus with three alleles and a dimeric locus with two alleles. On the basis of genetic distances, similarity between these populations and levels of variation were assessed both within populations (GST = 0.0376) and between populations (DST = 0.0194). Gene flow between populations was low (Nm = 6.399).